Personal Assistance Policy in the UK: What’s the Problem with Direct Payments? - Pearson, Charlotte; Barnes, Colin; Jolly, Debbie; Mercer, Geof; Priestley, Mark; Riddell, Sheila (Disability Studies Quarterly, 2005)
Across the United Kingdom (UK), the development of personal assistance through the policy of Direct Payments has seen a varied pattern in its success since its implementation in 1997. In some areas, local authorities have been reluctant to develop schemes, whereas others have shown a more positive commitment to ensure widespread access has been made. This article offers an overview of research in this area and reports on initial findings from a major UK wide study on Direct Payments being carried out by researchers at the Universities of Edinburgh, Glasgow and Leeds and funded by the Economic and Social Research Council (ESRC). In doing this, a series of conflicts will be set out, which have affected the move towards securing independent living for disabled people in the UK.